2011
DOI: 10.1007/s10162-011-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

Across-Channel Timing Differences as a Potential Code for the Frequency of Pure Tones

Abstract: When a pure tone or low-numbered harmonic is presented to a listener, the resulting travelling wave in the cochlea slows down at the portion of the basilar membrane (BM) tuned to the input frequency due to the filtering properties of the BM. This slowing is reflected in the phase of the response of neurons across the auditory nerve (AN) array. It has been suggested that the auditory system exploits these across-channel timing differences to encode the pitch of both pure tones and resolved harmonics in complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…An early example of a theory that proposed the importance of such a "place-rate match" was described by Moore (1982), who suggested that the analysis of inter-spike intervals produced by a given auditory nerve (AN) fiber was limited to intervals between about 0.5/CF and about 15/CF. Finally, some authors have suggested that the frequencies of resolved, but not of unresolved, harmonics may be encoded by differences in the timing of the responses of AN fibers as a function of their CF (Shamma, 1985;Oxenham et al, 2004;Cedolin and Delgutte, 2010; but see Carlyon et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…An early example of a theory that proposed the importance of such a "place-rate match" was described by Moore (1982), who suggested that the analysis of inter-spike intervals produced by a given auditory nerve (AN) fiber was limited to intervals between about 0.5/CF and about 15/CF. Finally, some authors have suggested that the frequencies of resolved, but not of unresolved, harmonics may be encoded by differences in the timing of the responses of AN fibers as a function of their CF (Shamma, 1985;Oxenham et al, 2004;Cedolin and Delgutte, 2010; but see Carlyon et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The integration in a "spatiotemporal" representation allows the extraction of a more reliable percept of pitch exploiting the place-rate and temporal coding redundancy 35,36 and admits more realistic decoding mechanisms (without need of delay lines), such as across-channel coincidence detection. However, recently Carlyon et al 37 have shown that straightforward pitch estimates obtained from this representation are strongly influenced by the overall level. Hence, the means whereby the pitch could be extracted under this approach are far from being understood.…”
Section: B Survey Of Previous Resultsmentioning
confidence: 99%
“…In principle, such mechanisms can thus overcome some major limitations affecting temporal mechanisms based on within-channel periodicity information in individual channels and purely spectral mechanisms based on tonotopic maxima in firing rate. However, physiological evidence for their existence remains scant, and it remains questionable whether such a mechanism can provide a sufficiently robust representation of pitch, given the level-dependencies found in physiological auditory-nerve recordings (Carlyon et al, 2012). The questions of the presence of harmonic templates, implied by the use of EP or MASD profiles, and of how tonotopic representations of the stimuli would map to such templates, also remain unsolved.…”
Section: Overall Summary and Conclusionmentioning
confidence: 98%
“…The effects of level on the bandwidth, phase characteristics, and best frequency of the cochlear filters are likely to complicate the neural implementation and interpretation of a more general and physiologically realistic MASD mechanism. For instance, Carlyon et al (2012) analyzed auditory-nerve data from guinea-pig recordings and found that level-dependencies rendered across-channel timing cues relatively unreliable as a method for determining the frequency of pure tones. Similar limitations are likely to apply to the current scheme.…”
Section: Mean-absolute-spatial-derivative (Masd) Profilementioning
confidence: 99%